(untitled) (Bangladesh Journal of Agricultural Research, 2016)
An experiment with Hippeastrum flower (Hippeastrum hybridum Hort.) cv. Apple Blossom comprising three sucrose concentrations viz. 0 (control), 2 and 4 % and five aluminium sulphate concentrations viz. 0 (control), 0.25, 0.50, 0.75 and 1.0 mM at the Horticulture Laboratory of Bangabandhu Sheikh Mujibur Rahman Agricultural University, Bangladesh during the period from April 01 to April 30, 2009. The experiment was laid out in a Completely Randomized Design (CRD) with three replications. Sucrose, aluminium sulphate and their combinations had significant influence on most of the parameters studied. Transpiration loss and water uptake ratio decreased significantly with the increased sugar levels and aluminium sulphate upto 0.75 mM beyond which they were increased. Transpiration loss and water uptake ratio was found minimum in the vase solution containing 4% sucrose (0.78) and 0.75 mM aluminium sulphate (0.80), which ultimately resulted in an enhanced vase life (9.2 days for sucrose and 9.11 days for aluminium sulphate) of cut Hippeastrum flower. A linear relationship between water uptake and vase life of flowers was found (y = 0.056x + 5.791). Sucrose 4% and aluminium sulphate 0.75 mM in combination gave maximum total water uptake, maximum days to onset of deterioration, the highest average fresh weight of single scape at 6th and 10th day after setting the trial. Transpiration loss and solution uptake ratio was found maximum in the combination of 4% sucrose and 0.75 mM aluminium sulphate (0.48) with the longest vase life of 10.33 days of cut Hippeastrum flower cv. Apple Blossom. Bangladesh J. Agril. Res. 41(2): 221-234, June 2016